2022
DOI: 10.3389/fnagi.2022.837467
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Locomotor Learning With Transcutaneous Spinal Electrical Stimulation and Somatosensory Augmentation: A Pilot Randomized Controlled Trial in Older Adults

Abstract: This study investigated locomotor learning of a complex terrain walking task in older adults, when combined with two adjuvant interventions: transcutaneous spinal direct current stimulation (tsDCS) to increase lumbar spinal cord excitability, and textured shoe insoles to increase somatosensory feedback to the spinal cord. The spinal cord has a crucial contribution to control of walking, and is a novel therapeutic target for rehabilitation of older adults. The complex terrain task involved walking a 10-meter co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…We also asked participants about the onset, duration, and location of experienced AEs and observed that there were temporally more-extended AE reports as well as more reports of sensations under both electrodes in the active conditions. While previous tsDCS studies mostly focused on the presence or absence of AEs [29, 31], we believe that a spatio-temporal characterization of AEs as carried out here is important for allowing to design an appropriate tsDCS control condition that ensures adequate blinding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also asked participants about the onset, duration, and location of experienced AEs and observed that there were temporally more-extended AE reports as well as more reports of sensations under both electrodes in the active conditions. While previous tsDCS studies mostly focused on the presence or absence of AEs [29, 31], we believe that a spatio-temporal characterization of AEs as carried out here is important for allowing to design an appropriate tsDCS control condition that ensures adequate blinding.…”
Section: Discussionmentioning
confidence: 99%
“…This allowed us to provide detailed descriptions of overall AE reports as well as condition-differences using Frequentist and Bayesian statistics, including spatio-temporal AE aspects and blinding success. To our knowledge, this combination of factors goes far beyond what has previously been carried out in the tsDCS literature: out of 76 human tsDCS studies, only nine [24][25][26][27][28][29][30][31][32] employed structured questionnaires, with only three of these statistically comparing effects under active and sham conditions [25,28,29] and none investigating spatio-temporal aspects. Our study thus provides a starting point for a systematic and comprehensive assessment of tsDCS AEs, and we believe that the tsDCS community might benefit from a standardized and psychometrically evaluated questionnaire.…”
Section: Adverse Effects (Aes) Of Tsdcsmentioning
confidence: 98%
See 1 more Smart Citation
“…As shown in Table 2 , the effects of tsDCS on motor improvement in humans were identified in 10 out of 17 studies. Most studies targeted the thoracic vertebrae (T-11-T12; [ 45 , 46 , 47 , 48 , 49 , 50 , 52 , 53 ] (but see [ 51 , 54 ]) showing that anodal tsDCS can be effective in preventing fatigue and in enhancing different whole-body movements [ 45 , 48 ]. It can also improve sleep and restless leg symptoms (RLSs) in idiopathic RLS subjects [ 50 ].…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…It can also improve sleep and restless leg symptoms (RLSs) in idiopathic RLS subjects [ 50 ]. In Clark et al’s study [ 52 ], thirty minutes of anodal tsDCS combined with a complex terrain motor task determined larger and more consistent retention of performance than the sham condition.…”
Section: Data Extraction and Analysismentioning
confidence: 99%